La educación virtual y su incidencia en la desmotivación de los estudiantes del tercer año de bachillerato de la Unidad Educativa Eugenio Espejo en el periodo lectivo 2021-2022 - Palacios Ortega, Raquel Alexandra (2022)
The main objective of this case study was to investigate the demotivation of third year high school students of the educational unit "Eugenio Espejo" during their participation in virtual learning. Specifically, we sought to conceptualize the (dis)motives that could have an impact on the participant's learning process and to reconceptualize, in this sense, the activities proposed as motivational strategies. To this end, this study sought to examine whether there were changes in their motivation within the framework of activity theory. Scrutiny of the data revealed that the changes resulting from the COVID-19 pandemic negatively influenced the institution's learning process. Although they were relatively motivated in their early days as students, the new changes to which they had to adapt in the midst of the outbreak externally affected their learning experiences, leading to demotivation. The present study argues how this change can be captured by reference to Engstrom’s triangular model. Further discussions and implications are offered in the study.